KEBUTUHAN DEBIT UNTUK FLUIDISASI 01 MUARA SUNGAI- DAN ALUR PELAYARAN - Widiyanto, Wahyu (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Fluidization method is one of the alternatives to maintain river mouth and harbour entrance. It is expected to substitute the role of maintenance dredging that is high cost and often inefficient for small volume of dredging. A series of research is conducted to understand the fluidization method but there has been little confidence whether fluidization process can run when the system is implemented in the field. Hence, fluidization model of large scale is expected to enhance confidence. The objective of the present study is to obtain flow rate required for fluidization. The study used two dimensional physical modelling of large scale. It was conducted by testing various sediment thickness (burial depth of pipe) from 25 cm to 150 cm in a large concrete well. Several parameters were observed on the experiments. Performances of one and three holes of fluidizer pipe were observed too. The flow rate requirement increases linearly with sediment thickness. For 1 hole of fluidizer pipe, the flow rate requirement approaches Qh =0,45 db + 0,40. While 3 holes of fluidizer pipe requires flow rate as Qh =1,44 db + 0,16. Where db is sediment thickness. Comparison between the performances of 1 hole and 3 holes of pipe show that holes spacing significant to fluidization. The distance between holes should not be too long. Cooperation of holes may reduce flow rate requirement. Keywords : fluidization, dredging, sediment